2018
DOI: 10.5296/ajfa.v10i1.13029
|View full text |Cite
|
Sign up to set email alerts
|

Public Sector Auditing and Corruption: A Literature Review

Abstract: The notion that auditing could reduce corruption has received considerable attention in both business and academia. The purpose of the current study is to explore the latest trends and gaps in the literature that investigate the link between corruption and public sector auditing. It is based on reviews of the academic literature and draws general conclusions on the status of the latest findings. The previous literature on corruption focused on economic and political perspectives. Although evidence suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
(92 reference statements)
1
8
0
1
Order By: Relevance
“…There is a relatively low number of studies on how SAIs influence governmental effectiveness and corruption. This study found, in line with [54][55][56], that although there is evidence that audits in the public sector may contribute to fighting corruption, there are few studies investigating the role of SAIs in detecting and fighting this phenomenon and in deeply analyzing the contribution of different types of audits to fight against corruption. Assakaf et al [54] argue that no one has managed to give a specific answer to how SAIs contribute to preventing and fighting corruption, and there are no studies researching the link between the performance of audits in the public sector and corruption.…”
Section: Supreme Audit Institutionssupporting
confidence: 62%
“…There is a relatively low number of studies on how SAIs influence governmental effectiveness and corruption. This study found, in line with [54][55][56], that although there is evidence that audits in the public sector may contribute to fighting corruption, there are few studies investigating the role of SAIs in detecting and fighting this phenomenon and in deeply analyzing the contribution of different types of audits to fight against corruption. Assakaf et al [54] argue that no one has managed to give a specific answer to how SAIs contribute to preventing and fighting corruption, and there are no studies researching the link between the performance of audits in the public sector and corruption.…”
Section: Supreme Audit Institutionssupporting
confidence: 62%
“…The necessity for IA function arises more in the public sector due to the complexity of the commonly broad objectives (Schillemans and van Twist, 2016) and the multiplicity of the audience whose expectations are varied (Menza et al , 2019; Pilcher et al , 2013). Hence, public funds must be safeguarded, and the management of the public sector enterprises should ensure an efficient IA (Abuazza et al , 2015; Assakaf et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In line with a significant result of the follow-up audit on fraud against the local government budget, this means that the follow-up audit had a negative effect on the fraud against the local government budget. Assakaf et al (2018) state that audit entities have a critical position in the follow-up process to audit results (Zahra et al, 2021).…”
Section: Discussionmentioning
confidence: 99%